(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The system of concepts, used for the estimation of plants rarity is analyzed and the basic categories of rareness are distinguished: true, diffuse, peripheral and temporal. Lack of scientific information on ecological and coenotic connections of rare plants is shown and the necessity of complex estimation of rare plant population systems is justified.